Design and Validation of Educational Material Aimed at Increasing Self-Efficacy of People With Diabetes Mellitus Type 2 - Hertuida Clara; Hasan, Hafizah Che; Nambiar, Nisha (Holistic Nursing Plus, 2025)
Background: Diabetes mellitus (DM) is a chronic metabolic disease that is at risk of causing various complications including microvascular and macrovascular complications. It therefore needs to be controlled through the implementation of diabetes self-management on a regular daily basis. The factor that plays a role in influencing diabetes self-management is self-efficacy, therefore it is necessary to make efforts to increase self-efficacy through an educational program. Purpose: The purpose of this study was to design and validate educational materials to improve self-efficacy in patients with type 2 diabetes mellitus. Methods: The method used consists of two phases, namely 1) design; and 2) validation of educational materials. The design of the educational materials followed the recommendations provided by Hoffman while the content followed the guidelines of the Association of Diabetes Educators. Validation was conducted including validation by experts and validation by representatives of the DM patient population using validity instruments. Results: The educational materials compiled consisted of six units, namely self-efficacy; diet (meal planning); exercise; therapy, independent blood sugar monitoring; and foot care. The results of validation by experts obtained an approval rate of 87.65%, while the results of validation from population representatives reached 99.04% approval. Conclusions: The educational materials compiled or designed have met the provisions of valid or feasible to be used as educational materials for type 2 DM patients. Keywords: Diabetes Mellitus Self-Efficacy, Education, validation of educational materials